An air spring support assembly
Patent Information
- Application Number
- CN202410596731.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-14
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-05-14
AI Technical Summary
由于气弹簧在使用过程中,其外壳需要承受较大的压力,因此大多数气弹簧的外壳采用金属材质制成,而金属材质的外壳其质量重、难加工、不易维护、容易生锈等
本申请采用塑料外壳具有质轻、易加工等优点,该抗压角安装槽的形成,增大塑料外壳的受力面积,有利于提高外壳的抗力能,减少出现破裂、开裂、漏油等现象。并且抗压角安装不与弹簧支撑单元抵接,因此,当空气弹簧支撑组件在工作时不会受到影响,同时抗压角安装槽的设置,还能提高空气弹簧支撑组件的安装便捷性,当安装空气弹簧支撑组件于电子产品中时,抗压角安装槽便于卡接固定和调节安装角度,提高安装的便捷性,相比于表面光滑的塑料外壳更容易安装固定,提高空气弹簧支撑组件的实用性。
Smart Images

Figure CN118582489B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of springs, and more specifically, to an air spring support assembly. Background Technology
[0002] A spring is a mechanical part that works by utilizing elasticity. Parts made of elastic materials deform under external force and return to their original shape after the force is removed, providing functions such as shock absorption and extension / retraction. Therefore, they are widely used in transportation, technology, daily necessities, and home appliances where drive, extension, and shock absorption are required. However, current springs have the following technical drawbacks: they are prone to rusting, have a short lifespan, are easily deformed after repeated use and wear, experience aging and fatigue with repeated use, resulting in decreased elasticity and flexibility, significantly reduced work efficiency, performance, and lifespan after repeated use, high cost, and limited application scenarios, requiring special customization.
[0003] Therefore, using air springs instead of regular springs can reduce the above problems. Replacing ordinary springs with air springs can reduce the volume of ordinary spring chambers by 50%. Air springs are more suitable for tight radial and axial spaces. Air spring assemblies are lightweight, which can save production time and costs. At specific working heights, they provide more accurate tolerance ranges and predictable loads.
[0004] An air spring, also called a gas spring, is an industrial component that provides support, cushioning, braking, height adjustment, and angle adjustment. It consists of the following parts: a pressure cylinder (also called a housing), a piston rod, a piston, a sealing guide sleeve, a filling material (inert gas or an oil-gas mixture), internal and external control elements (referring to controllable air springs), and connectors. The principle is to fill the sealed pressure cylinder with inert gas or an oil-gas mixture, making the pressure inside the chamber several times or tens of times higher than atmospheric pressure. The piston rod's movement is achieved by utilizing the pressure difference created by the smaller cross-sectional area of the piston rod compared to the piston's cross-sectional area. Due to this fundamental difference in principle, air springs have significant advantages over ordinary springs: relatively slower speed, less dynamic force variation, and easier control.
[0005] Gas springs, also known as support rods, gas supports, angle adjusters, gas bars, dampers, etc., are currently being developed by adding a spring inside the outer shell to form an air spring support assembly, thereby improving damping effect, load-bearing capacity, and adjustment speed. Because the outer shell of a gas spring needs to withstand significant pressure during use, most gas spring shells are made of metal. However, metal shells are heavy, difficult to process, difficult to maintain, and prone to rust.
[0006] With the advancement of technology, current electronic products and medical devices tend to be miniaturized. As a result, air springs are becoming smaller and lighter. Currently, plastic shells are used instead of metal shells, which makes them less prone to rusting and has the advantages of being lightweight and small. However, the surface of current plastic shells is smooth, making them difficult to install. Furthermore, they are prone to cracking and oil leakage when subjected to high pressure for a long time, thus reducing their practicality. Summary of the Invention
[0007] In order to reduce the occurrence of oil leakage and damage in air spring support assemblies and to facilitate the installation of air spring support assemblies, this application provides an air spring support assembly.
[0008] This application provides an air spring support assembly, including a plastic housing and a spring support unit. The plastic housing has a cavity, and the spring support unit is installed in the cavity of the plastic housing. The outer side wall of the plastic housing is convex towards the cavity and at least one anti-compression angle mounting groove is formed on the outer wall. The inner wall of the plastic housing corresponding to the anti-compression angle mounting groove does not abut against the spring support unit.
[0009] This application utilizes a plastic shell, which offers advantages such as light weight and ease of processing. The formation of the pressure-resistant angle mounting groove increases the stress-bearing area of the plastic shell, thereby improving its strength and reducing the likelihood of cracking, splitting, or oil leakage. Furthermore, the pressure-resistant angle mounting does not contact the spring support unit, ensuring that the air spring support assembly is not affected during operation. The pressure-resistant angle mounting groove also enhances the ease of installation. When installed in electronic products, the groove facilitates locking, fixing, and angle adjustment, improving installation convenience. Compared to a smooth plastic shell, it is easier to install and fix, thus increasing the practicality of the air spring support assembly.
[0010] Preferably, the spring support unit includes a piston rod drive and a spring. Both the piston rod drive and the spring are installed in the cavity of the plastic housing. One end of the spring is fixed to the bottom of the groove in the cavity of the plastic housing, and the other end of the spring is supported and connected to the piston rod drive. The end of the piston rod drive away from the spring extends out of the cavity of the plastic housing. Neither the piston rod drive nor the spring abuts against the anti-compression angle mounting groove.
[0011] In the above solution, the interaction between the piston rod drive component and the spring component gives the air spring support assembly better elasticity and load-bearing capacity, and after compression, the elasticity recovers quickly, improving service life. Furthermore, neither the piston rod drive component nor the spring component comes into contact with the anti-compression angle mounting groove, so the piston rod drive component and the spring component are not affected by the anti-compression angle mounting groove during operation.
[0012] Preferably, the plastic shell has at least one protrusion at the bottom of the pressure-resistant angle mounting groove.
[0013] By incorporating at least one protrusion, the thickness of the plastic casing at the protrusion is increased, thereby enhancing the load-bearing area and compressive strength of the casing. This reduces the likelihood of cracking under high pressure, thus minimizing the possibility of oil leaks. Simultaneously, it facilitates the snap-fit installation of the air spring assembly, improving the installation stability of the air spring support assembly.
[0014] Preferably, the ratio of the depth of the pressure-resistant angle mounting groove to the thickness of the plastic shell is 1:(1.3-1.6).
[0015] The above thickness ratio represents a preferred range in this application, and the resulting pressure-resistant angle mounting groove provides excellent reinforcement to the plastic housing. Furthermore, this ratio of pressure-resistant angle mounting groove does not affect the normal operation of the spring support unit. It also enhances the pressure resistance of the plastic housing, reducing the likelihood of cracking, oil leakage, and other issues.
[0016] Preferably, the ratio of the height of the protrusion to the thickness of the plastic shell is 1:(1.3-1.6).
[0017] The above ratio range is the preferred range of this application. The formed bumps can increase the thickness of the plastic shell, improve its compressive strength, and reduce the occurrence of damage, oil leakage and other phenomena in the shell of the air spring support assembly.
[0018] Preferably, the plastic shell is a POM shell formed by injection molding.
[0019] Acetal resin, also known as polyoxymethylene (POM), polyoxymethylene, or polyacetal, is a thermoplastic crystalline polymer, often referred to as "super steel" or "acetal." POM is a linear polymer without side chains, characterized by high density and high crystallinity, possessing excellent comprehensive properties. It exhibits good mechanical properties, including strength, modulus, high and low temperature resistance, wear resistance, toughness, fatigue resistance, creep resistance, electrical insulation, solvent resistance, and processability.
[0020] Therefore, using acetal resin can reduce cracking and oil leakage. At the same time, the formed pressure-resistant corner mounting groove combines the pressure resistance of the plastic shell in both material and mechanical fields, and enables the air spring support assembly to achieve better pressure resistance. In addition, the pressure-resistant corner mounting groove formed by acetal resin has a stable structure and is not prone to deformation or damage during installation, thus reducing the possibility of oil leakage or damage to the pressure-resistant corner mounting groove.
[0021] Preferably, the POM is modified POM, which is composed of the following parts by weight of raw materials: 100 parts of POM. 1-3 parts expanded graphite 1-3 parts of polyborosilazane powder 2-8 parts of maleic anhydride graft.
[0022] The above-mentioned raw material is the preferred choice for this application. Expanded graphite is graphite that has been expanded after processing. It is a loose, porous, worm-like material that, in addition to possessing the excellent properties of natural graphite such as resistance to cold and heat, corrosion resistance, and self-lubrication, also has properties that natural graphite does not have, such as softness, compression resilience, and radiation resistance. Therefore, its use in the composite modification of acetal resin can further improve the corrosion resistance, cold and heat resistance, flexibility, and aging resistance of acetal resin.
[0023] Maleic anhydride grafts can improve the compatibility of expanded graphite with acetal resin, while polyborosilicate powder has good filling properties and can be mixed evenly with the modified POM raw material system, resulting in modified POM with better impact performance. Simultaneously, polyborosilicate powder exhibits high high-temperature resistance and oxidation resistance. The polyborosilicate powder is obtained by crosslinking and curing organic polyborosilicate and platinum catalyst in a 20:1 weight ratio, drying at 300℃ for 2 hours, and then pulverizing to obtain 500-800 mesh polyborosilicate powder. When used to modify POM, this polyborosilicate powder gives the resulting plastic shell better compressive strength.
[0024] The polyborosilicate powder has a molecular weight (Mn) of 700-900, a viscosity of 11000-21000cp at 25℃, and a ceramic yield (800℃) of >52% in the cured product; the ceramic density is 1.75-2.03 g / cm-3; the platinum catalyst is a platinum-carbon catalyst with a Pt purity of 20%.
[0025] Polyoxymethylene (POM) is a smooth, glossy, hard, and dense material, pale yellow or white in color, suitable for long-term use within a temperature range of -40 to 100°C. Its wear resistance and self-lubricating properties are superior to most engineering plastics, and it also exhibits good oil and peroxide resistance. However, it is not resistant to acids, strong alkalis, or ultraviolet radiation from sunlight.
[0026] Polyoxymethylene (POM) boasts a tensile strength of up to 70 MPa, low water absorption, dimensional stability, and a glossy finish—all properties superior to nylon. As a highly crystalline resin, POM is among the toughest thermoplastic resins. It exhibits high heat resistance, flexural strength, and fatigue resistance, but its impact strength is low. POM's notched impact strength and flexural strength are relatively low, making it prone to cracking or breakage at stressed areas. Therefore, this application utilizes a composite of maleic anhydride grafts, expanded graphite, and polyborosilicate powder, produced under the action of a platinum catalyst. The resulting shell exhibits superior load-bearing capacity and, when used in air spring support components, can reduce damage, cracking, and oil leakage.
[0027] The modified POM is prepared by the following method: Weigh out the maleic anhydride graft by weight and heat it to melt. Then add expanded graphite and stir evenly. Next, add polyborosilazane powder and mix evenly. Then add acetal resin and transfer it to an extruder for melt extrusion, drying, granulation, and so on until modified POM is obtained.
[0028] The cross-linking and curing of polyborosilicate powder is accelerated by using a platinum catalyst, and the modified POM obtained by the above process also has better compressive strength.
[0029] Preferably, the maleic anhydride graft is one or more of the following: rosin-modified maleic acid resin, triethoxysilane polyethylene glycol maleimide, methyl vinyl ether-maleic anhydride copolymer, and maleic anhydride-grafted ethylene and octene copolymer.
[0030] Rosin-modified marinic acid resin WMR-422 from Xiamen Weier Chemical Co., Ltd.; POM brand and model preferred is Polyplastics SF-15 from Japan.
[0031] The average molecular weight of triethoxysilane polyethylene glycol maleimide is 200-3400, and its molecular structure is as follows: The average molecular weight of maleic anhydride-grafted ethylene and octene copolymers is 0.13-0.20 million, and the molecular structure is as follows: Maleic anhydride-grafted ethylene and octene copolymer is a maleic anhydride-grafted elastomer POE (ethylene and octene copolymer) manufactured by Dow Chemical Company in the United States, model AMPLIFY GR216.
[0032] Preferably, the weight ratio of the rosin-modified maleic acid resin, triethoxysilane polyethylene glycol maleimide, maleic anhydride-grafted ethylene and octene copolymer is (2.3-3.3):1:(1.7-2.6).
[0033] When rosin-modified maleic acid resin, triethoxysilane polyethylene glycol maleimide, maleic anhydride-grafted ethylene, and octene copolymer are compounded, a better synergistic effect is achieved, resulting in improved physical properties of the modified POM. The resulting housing, used in air spring support components, reduces the occurrence of damage, cracking, and oil leaks.
[0034] Preferably, the expanded graphite grains have a diameter of 0.01-0.03 mm and a worm length of 0.09-0.15 mm.
[0035] The above-mentioned selection of expanded graphite is preferred for this application. When it is compounded with the raw material system of modified POM, the possibility of breakage, cracking, oil leakage and other problems can be reduced.
[0036] In summary, this application has the following beneficial effects: This application utilizes a plastic shell, which offers advantages such as light weight and ease of processing. The formation of the pressure-resistant angle mounting groove increases the stress-bearing area of the plastic shell, thereby improving its strength and reducing the likelihood of cracking, splitting, or oil leakage. Furthermore, the pressure-resistant angle mounting does not contact the spring support unit, ensuring that the air spring support assembly is not affected during operation. The pressure-resistant angle mounting groove also enhances the ease of installation. When installed in electronic products, the groove facilitates locking, fixing, and angle adjustment, improving installation convenience. Compared to a smooth plastic shell, it is easier to install and fix, thus increasing the practicality of the air spring support assembly. Attached Figure Description
[0037] Figure 1 This is a schematic diagram of an air spring support assembly according to this application.
[0038] Figure 2 This is a cross-sectional structural diagram of an air spring support assembly according to this application.
[0039] Figure 3 This is a picture of an air spring support assembly after disassembly according to this application.
[0040] Figure 4 It is a test method for low-temperature durability.
[0041] Explanation of reference numerals in the attached figures: 1. Plastic housing; 11. Anti-compression angle mounting groove; 12. Protrusion; 2. Piston rod drive component; 21. Piston rod; 22. Tie rod cap; 23. Cylinder head; 24. Cylinder guide; 25. Diaphragm; 26. Piston; 27. Valve; 3. Spring component; 31. Spring; 32. Spring carrier; 33. Pin. Detailed Implementation
[0042] The following is in conjunction with the appendix Figure 1-2The present application will be further described in detail with reference to the embodiments. Example
[0043] Example 1 An air spring support assembly, as shown in the reference Figure 1 and Figure 2 The device includes a plastic housing 1 and a spring support unit. The spring support unit includes a piston rod drive 2 and a spring 3. The plastic housing 1 has a cavity. The piston rod drive 2 and the spring 3 are both installed in the cavity. One end of the spring 3 is fixed to the bottom of the cavity of the plastic housing 1, and the other end of the spring 3 is supported and connected to the piston rod drive 2. The end of the piston rod drive 2 away from the spring 3 extends out of the cavity of the plastic housing 1.
[0044] like Figure 2 As shown, the piston rod drive component 2 includes a piston rod 21, a tie rod cap 22, a cylinder head 23, a cylinder guide 24, a diaphragm 25, a piston 26, and a valve 27. The tie rod cap 22, cylinder head 23, cylinder guide 24, diaphragm 25, piston 26, and valve 27 are sequentially arranged on the piston rod 21. The cylinder head 23 is fixed to the cavity opening of the plastic housing 1. A section of the piston rod 21 away from the cylinder head 23 extends out of the cavity of the plastic housing 1, and the tie rod cap 22 is installed at the end of the piston rod 21 away from the plastic housing 1. The cylinder head 23 covers the cylinder guide 24. The diaphragm 25 is fixed to the end of the cylinder guide 24 away from the cylinder head 23. The valve 27 is located at the end of the piston rod 21. The piston 26 is located between the valve 27 and the diaphragm 25, which plays a better sealing role and reduces the possibility of air leakage, oil leakage, etc. Figure 3 This is a physical image of the object used in this application.
[0045] The spring component 3 includes a spring 31, a spring 31 carrier, and a pin 33. The pin 33 fixes one end of the spring 31 to the bottom of the groove in the cavity of the plastic housing 1. The spring 31 carrier is installed at the end of the spring 31 away from the pin 33 and is supported and connected to the valve 27. The cavity is sealed with a filler such as nitrogen and silicone oil.
[0046] The outer wall of the plastic shell 1 protrudes into the cavity and forms at least one anti-pressure angle mounting groove 11 on the outer wall. The number of anti-pressure angle mounting grooves 11 can be one, two, three, etc. In this embodiment, one is preferred, and neither the piston rod drive member 2 nor the spring member 3 abuts against the anti-pressure angle mounting groove 11. The anti-pressure angle mounting groove 11 is located in the lower section of the plastic shell 1 and does not contact the spring 31. The distance from the anti-pressure angle mounting groove 11 to the bottom of the plastic shell 1 is 2mm.
[0047] The plastic outer shell 1 has at least one protrusion 12 corresponding to the bottom of the anti-compression angle mounting groove 11. The number of protrusions 12 can be 1, 2, 3, etc., and in this embodiment, 1 is preferred.
[0048] The ratio of the depth of the pressure-resistant angle mounting groove 11 to the thickness of the plastic shell can be 1:1.3, 1:1.4, 1:1.5, or 1:1.6, and in this embodiment, 1:1.4 is preferred. The ratio of the height of the protrusion 12 to the thickness of the plastic shell can be 1:1.3, 1:1.4, 1:1.5, or 1:1.6, and in this embodiment, 1:1.4 is preferred. These ratios result in better pressure resistance for the plastic shell 1.
[0049] Example 2 The difference between Example 2 and Example 1 is that the plastic shell is a POM plastic shell obtained by injection molding; at the same time, the piston, guide, cylinder head, pin, tie rod cap, and spring support are all made of POM by injection molding. The injection temperature is 220℃; the mold temperature is 100℃; the injection pressure is 100MPa; the injection speed is fast injection; the holding time is 10s; the cooling time is 50s; and the plasticizing time is 18s.
[0050] Example 3 The difference between Example 3 and Example 2 is that the acetal resin is modified POM. The modified POM is obtained by the following method: 0.2 kg of maleic anhydride graft is weighed and heated to 150°C until it is completely melted. Then, 0.1 kg of expanded graphite is added and stirred evenly. Then, 0.3 kg of polyborosilazane powder is added and mixed evenly. Then, 10 kg of acetal resin is added and transferred to an extruder for melt extrusion. The temperature settings of the extruder are: Zone 1 180°C, Zone 2 190°C, Zone 3 195°C, Zone 4 190°C, Zone 5 195°C, Zone 6 195°C, Zone 7 190°C, and the die head 180°C. After water cooling, it is placed in an oven at 50°C for drying for 2 hours and then put into a granulator for granulation to obtain modified POM.
[0051] The maleic anhydride graft is a rosin-modified maleic acid resin with expanded graphite grains of 0.01 mm in diameter and worm length of 0.09 mm.
[0052] The injection molding temperature of modified POM is 195℃.
[0053] Example 4 The difference between Example 4 and Example 3 is that the amount of raw materials used is different, as follows: 10kg acetal resin, 0.2kg expanded graphite, 0.2kg polyborosilicate powder, 0.5kg maleic anhydride graft, expanded graphite grain diameter 0.02mm, worm length 0.12mm.
[0054] Example 5 The difference between Example 5 and Example 3 is that the amount of raw materials used is different, as follows: 10kg acetal resin, 0.3kg expanded graphite, 0.1kg polyborosilicate powder, 0.8kg maleic anhydride graft, expanded graphite grain diameter 0.03mm, worm length 0.15mm.
[0055] Example 6 The difference between Example 6 and Example 4 is that the maleic anhydride graft consists of 0.4 kg of rosin-modified maleic acid resin and 0.1 kg of triethoxysilane polyethylene glycol maleimide.
[0056] Example 7 The difference between Example 7 and Example 4 is that the maleic anhydride graft consists of 0.2 kg of methyl vinyl ether-maleic anhydride copolymer and 0.3 kg of maleic anhydride-grafted ethylene and octene copolymer.
[0057] Example 8 The difference between Example 8 and Example 4 is that the maleic anhydride graft consists of 0.3 kg of rosin-modified maleic acid resin, 0.1 kg of triethoxysilane polyethylene glycol maleimide, and 0.1 kg of methyl vinyl ether-maleic anhydride copolymer.
[0058] Example 9 The difference between Example 9 and Example 4 is that the maleic anhydride graft is composed of 0.3 kg of rosin-modified maleic acid resin, 0.1 kg of triethoxysilane polyethylene glycol maleimide, and 0.1 kg of maleic anhydride-grafted ethylene and octene copolymer.
[0059] Example 10 The difference between Example 10 and Example 4 is that the maleic anhydride graft consists of 0.25 kg of rosin-modified maleic acid resin, 0.15 kg of triethoxysilane polyethylene glycol maleimide, and 0.1 kg of maleic anhydride-grafted ethylene and octene copolymer.
[0060] Example 11 The difference between Example 11 and Example 4 is that the maleic anhydride graft is composed of 0.35 kg of rosin-modified maleic acid resin, 0.1 kg of triethoxysilane polyethylene glycol maleimide, and 0.05 kg of maleic anhydride-grafted ethylene and octene copolymer.
[0061] Example 12 The difference between Example 12 and Example 4 is that the maleic anhydride graft consists of 0.2 kg of rosin-modified maleic acid resin, 0.1 kg of triethoxysilane polyethylene glycol maleimide, 0.1 kg of methyl vinyl ether-maleic anhydride copolymer, and 0.1 kg of maleic anhydride-grafted ethylene and octene copolymer.
[0062] Example 13 The difference between Example 13 and Example 3 is that the maleic anhydride graft material used is maleic anhydride grafted PE (brand and model: BASF B4300K4).
[0063] Example 14 The difference between Example 14 and Example 3 is that the polyborosilazane powder is replaced with an equal amount of expanded graphite.
[0064] Example 15 The difference between Example 15 and Example 3 is that expanded graphite is replaced with an equal amount of polyborosilazane powder.
[0065] Example 16 The difference between Example 16 and Example 3 is that the maleic anhydride graft is replaced with an equal amount of silane coupling agent KH-792.
[0066] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that there is no pressure angle mounting groove.
[0067] Performance testing The following performance tests were conducted on an air spring support assembly obtained in Examples 2-16 and Comparative Example 1.
[0068] Testing methods / test methods Spring parameters: Spring material SUS304, outer diameter average diameter Free length 127mm; effective coils 33, total 37; spring stiffness 10gf / mm; spring load L1=94.6mm; P1=322.7gf; L2=51.4mm, P2=753gf; Plastic casing thickness: 0.2mm; Pressure inside the plastic outer shell cavity: 45 kgf / mm; Cross-sectional area of the piston rod: Piston cross-sectional area: 1. Low-temperature durability test Dual-mode working time measuring machine (horizontal collision mode); collision speed: 0.5m / s; collision material: 10kg; thrust: 8N; measurement temperature: -23℃; stroke: 50mm.
[0069] The testing mechanism employed is a durability testing machine (A / C horizontal drive); operating speed: 1 second for pressing in, with automatic return upon return; test temperature: -23℃; stroke: 50mm; test cycle: 10min / cycle; number of tests: 1 million to 2 million cycles, test method as per reference. Figure 4 ; Judgment result: After 1 million cycles, check for any oil leakage or damage. If any of the above conditions are found, record it as unqualified; otherwise, record it as qualified.
[0070] 2. High temperature and low speed durability test: Extrusion speed: 1.5 sec; Cycle period: 10 min / cycle; Test stroke: 40 mm; Number of tests: 1 million to 2 million; Speed: 0.8 m / s; Load: 10 kg; Thrust: 8 N; Measurement stroke: 50 mm; Measurement temperature: 80 ℃.
[0071] Judgment result: After 1 million tests, check for any oil leakage or damage. If there is any, record the number of tests as 1 million. If there is no such situation, continue testing based on 1 million tests, stopping the test every 100,000 tests. When oil leakage or damage occurs, record the total number of tests.
[0072] 3. Impact strength The acetal resin or modified POM obtained in Examples 2-16 were injection molded and then subjected to the following performance tests; Notched impact strength of cantilever beam: conducted according to ASTM D256, with test conditions of 2mm V-notch, temperature of 25℃, test sample thickness of 3.2mm, 5 tests, and average value.
[0073] The experimental records are shown in the table below; Table 1. Experimental data of Examples 2-16 and Comparative Example 1 As can be seen from Example 2 and Comparative Example 1 and Table 1, the number of high temperature and low speed durability tests in Example 2 is greater than the number of high temperature and low speed tests in Comparative Example 1. This indicates that by opening and setting the pressure-resistant angle mounting groove, this application can not only reduce the occurrence of cracking and oil leakage in the plastic shell and improve the practicality of an air spring support assembly, but also facilitate the installation and adjustment of the air spring support assembly's installation angle.
[0074] Combining Examples 2 and 3 with Table 1, it can be seen that the notched impact strength of Example 2 is lower than that of Example 3, and the number of high temperature and low speed durability tests in Example 3 is greater than that in Example 2. This indicates that the modified POM of this application has better mechanical properties and reduces the occurrence of cracking and oil leakage in plastic shells.
[0075] Combining Examples 4 and 11 with Table 1, it can be seen that the notched impact strength of Example 4 is lower than that of Example 11, and the number of high-temperature and low-speed durability tests in Example 11 is greater than that in Example 4. This indicates that the maleic anhydride graft composed of rosin-modified maleic acid resin, triethoxysilane polyethylene glycol maleimide, methyl vinyl ether-maleic anhydride copolymer, and maleic anhydride-grafted ethylene and octene copolymer has better compatibility. Combined with expanded graphite and polyborosilicate powder, the modified POM obtains better impact performance, thus reducing the occurrence of damage, cracking, and oil leakage in the prepared plastic shell.
[0076] Combining Examples 13-16 and Example 3 with Table 1, it can be seen that the notched impact strength of Example 3 is higher than that of Examples 13-16, and the number of high-temperature and low-speed durability tests in Example 3 is greater than that in Examples 13-16. This indicates that by using the expanded graphite, polyborosilicate powder and compatibilizer of this application to modify POM, the resulting modified POM has better impact performance, and the plastic shell made of modified POM has better burst resistance, crack resistance and oil leakage resistance.
[0077] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. An air spring support assembly, characterized in that, The device includes a plastic housing (1) and a spring support unit. The plastic housing (1) has a cavity. The spring support unit is installed in the cavity of the plastic housing (1). The outer side wall of the plastic housing (1) is convex towards the cavity and at least one anti-compression angle mounting groove (11) is formed on the outer wall. The inner wall of the plastic housing (1) at the location corresponding to the anti-compression angle mounting groove (11) does not abut against the spring support unit. The plastic shell (1) has at least one protrusion (12) at the bottom of the anti-pressure angle mounting groove (11); The depth of the pressure-resistant angle mounting groove (11) is in the ratio of 1:(1.3-1.6) to the thickness of the plastic shell (1). The height of the protrusion (12) is in the ratio of the thickness of the plastic shell (1) to 1:(1.3-1.6); the plastic shell is a POM shell formed by injection molding. The POM is modified POM, which is composed of the following raw materials in parts by weight: 100 copies of POM 1-3 parts expanded graphite 1-3 parts of polyborosilazane powder 2-8 parts of maleic anhydride graft; The maleic anhydride graft is composed of rosin-modified maleic acid resin, triethoxysilane polyethylene glycol maleimide, maleic anhydride-grafted ethylene and octene copolymer in a weight ratio of (3-7):(1-2):
1.
2. The air spring support assembly according to claim 1, characterized in that: The spring support unit includes a piston rod drive (2) and a spring (3). Both the piston rod drive (2) and the spring (3) are installed in the cavity of the plastic shell (1). One end of the spring (3) is fixed to the bottom of the groove in the cavity of the plastic shell (1), and the other end of the spring (3) is supported and connected to the piston rod drive (2). The end of the piston rod drive (2) away from the spring (3) extends out of the cavity of the plastic shell (1). Neither the piston rod drive (2) nor the spring (3) abuts against the anti-compression angle mounting groove (11).
3. The air spring support assembly according to claim 1, characterized in that: The grain diameter of expanded graphite is 0.01-0.03 mm, and the worm length is 0.09-0.15 mm.
Citation Information
Patent Citations
Polyacetal resin composition and preparation method thereof
CN105255098A
Bottle, bottom die and bottle blowing die
CN116395236A
Impact-damping device, optimized device for damping impact of furniture door or drawer
CN1329206A
Low-temperature damper
CN210889883U